TIKTOK CONTENT CREATOR @YUSKYAUDAH'S STRATEGY AS A FORM OF SELF-EXISTENCE - Febriyanti, Nurul; Asy'ari, Nur Aini Shofiya; Azahari, Helmi (ASPIRATION Journal, 2025)
Social media is now an important aspect of individuals' daily activities, especially among generations Y and Z, who use it to express themselves and build their identities. The @Yuskyaudah account uses TikTok to build its existence and has been successful on FYP several times. The purpose of this study is to determine the content strategy of TikTok creator @Yuskyaudah as a form of self-existence through a study of Regina Luttrell's Circular Model of Some theory. Using a descriptive qualitative approach, this study examines the content production process, interactions with audiences, and strategies used by Yusky to construct his existence on the platform. Using a qualitative approach, data was collected through in-depth interviews and content observations and then validated using method triangulation techniques. The results of the study show that Titok @Yuskiyauda's content applies the concept of share, optimize, manage and engage to developself-existence.